The Interaction Radiation and Exposure Buildup Factors Properties of AM60 and AZ91 Alloys - Sriwongsa, Kittisak; Glumglomchit, Punsak; Suwannayuha, Mintharach; Kukuthapan, Phatchanok; Sukkasame, Nanawin; Ravangvong, Sunantasak; Glumglomjit, Sakchai (Asian Health, Science and Technology Reports, 2021)
In this research to study the total and partial interaction, radiation shielding and buildup factors properties of AM60 and AZ91 alloys. Radiation shielding effectiveness of alloys were computed by determine mass attenuation coefficient (mm), effective atomic number (Zeff), effective electron density (Nel) and mean free path (MFP) at photon energy ranging 10–3–105 MeV using WinXCom software program. Buildup factors (BFs) were estimated by Geometric Progression (G–P) fitting theory at energy ranging 15 keV–15 MeV up to 40 mfp deep penetration. The results from simulation technique indicated that, the radiation interaction with matter values can be discussed on fundamental of partial interaction processes as photoelectric absorption effect, Compton scattering and pair production which main processes at low, intermediate and high energies, respectively. In addition, AZ91 alloy was found excellent radiation shielding and can be developed for radiation shielding medium.